2021
DOI: 10.5217/ir.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Postgastrectomy gastric cancer patients are at high risk for colorectal neoplasia: a case control study

Abstract: Background/Aims: Several studies have shown that colorectal neoplasms (CRN) including colorectal cancer (CRC) may be prevalent in patients with gastric cancer. However, in most of these studies, colonoscopy to investigate the prevalence of CRN was performed prior to surgery. We aimed to investigate whether CRN was more prevalent in postgastrectomy gastric cancer patients than in healthy individuals.Methods: We reviewed the medical records of those patients within a cohort of gastric cancer patients with gastre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We did not identify any significant clinical differences in the cohorts with and without advanced colorectal neoplasia that would help further guide screening recommendations. It is important to note that this included similar frequencies of gastric cancer history given reports that patients with gastric cancer are at higher risk of colorectal neoplasia (11).…”
Section: Discussionmentioning
confidence: 87%
“…We did not identify any significant clinical differences in the cohorts with and without advanced colorectal neoplasia that would help further guide screening recommendations. It is important to note that this included similar frequencies of gastric cancer history given reports that patients with gastric cancer are at higher risk of colorectal neoplasia (11).…”
Section: Discussionmentioning
confidence: 87%
“…In 2020, it was estimated that about 10% of global cancer incidence, and about 9.4% of cancer-related deaths, could be attributed to CRC [ 2 ]. Risk factors for CRC include sex, age, race, and genetic factors [ 2 - 6 ]. Exposure to environmental risk factors, such as the shift to a modern lifestyle and a Westernized diet, plays a very important role in the increasing global incidence of CRC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] It was also reported that a postgastrectomy gastric cancer patient was a high risk for colorectal neoplasia. [5] But weak evidence exists regarding the relationship between EGN and colorectal adenoma.…”
Section: Introductionmentioning
confidence: 99%